Comparative Statics under Walras' Law: The Case of Strong Dependence - Quirk, J. P. (Review of Economic Studies, 1968)
Journal Article Comparative Statics under Walras' Law: the Case of Strong Dependence Get access J. P. Quirk J. P. Quirk University of Kansas Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 35, Issue 1, January 1968, Pages 11–21, https://doi.org/10.2307/2974403 Published: 01 January 1968